Influence of functional abilities on the quality of refereeing in handball - IVAN BELCIC; LANA RUZIC; ALEN MAROSEVIC (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: Several factors contributed to the evolution of handball, and one of the most important changes for faster, more dynamic and aggressive game is the change of rules which increase physical demands of players and especially referees. The aim of this study is to determine whether functional abilities have an influence on the quality of refereeing. Material and methods: 31 subjects were involved in the research, all of them top-level referees with an average age of 34.66±6.44, height 184.02±5.87 cm and body mass 91.14±10.61 kg. Testing was divided into two parts: the first part was spiroergometric progressive test on a treadmill to diagnose functional abilities, and the second part was the official handball matches. Results: Results show an average relative maximum oxygen uptake of 45.35±6.12 ml/min/kg. No statistically significant correlation was found between better functional abilities of handball referees and a better quality of refereeing. Conclusions: Referees have a lower anaerobic capacity, which could lead to errors in their judgment during the highest physiological loads in a match. Referees are a homogeneous group due to elimination criteria on tests at official seminars. If there were no elimination criteria, there would be greater variability among referees, and it would be possible to confirm the hypothesis that better functional abilities would lead to a better quality of refereeing.